Kurds and The Kharijites - Tahir, Anas Mohammad Sharif (Van Yuzuncu Yıl University, 2022)
Abstract The Kurdish people have played a crucial role in empowering themselves in both fields: governance and knowledge, and had an impact on all political events during the Rashidun Caliphate, the Umayyad Caliphate, as well as the Abbasid caliphate and after on. Kurdish history is characterized by the difficulty of its paths in collecting information about it as historians left large areas of their history without mentioning. It was known about them that they had many revolutions and unrest. Many feuding groups appeared among them. They are a proud nation that did not submit to things easily and did not wish to be ruled except by Kurdish rulers or the sheikhs of a Kurdish tribe of their own kind. It is, therefore, noticed that they were resisting the outward tide. Many of them joined the revolutionary movements. Despite this, the majority of them were of Sunnis throughout the ages, and Islam was the dominant religion among them after its appearance. Historical sources indicate the siding of some Kurdish sects with revolutionary movements in different periods from the beginning of Islam until the Abbasid era and beyond. The desire for rebellion appeared among them clearly. The Kharijites were among the most prominent of these groups, and the Kurds participated in revolutions and movements against Muslim rulers throughout the ages. This research comes as an attempt to understand the reasons for the appearance and spread of Kharijites among the Kurds and the extent of their participation in their revolutions. Keywords: (Kurds, Kharijites, spread, communication)